Pengaruh Etika Profesi dan Skeptisisme Profesional Auditor terhadap Ketepatan Pemberian Opini oleh Akuntan Publik pada Eksternal Auditor di Kantor Akuntan Publik Wilayah Tangerang Selatan - Dian Purwanti; Resa Nurmala (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of professional ethics and professional skepticism of auditors on the accuracy of giving opinions by public accountants to external auditors at the South Tangerang Regional Public Accountant Office. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination testing. and hypothesis testing. The results of this study that professional ethics have a significant effect on the accuracy of giving opinions by public accountants by 48.0%, hypothesis testing is obtained t count > t table or (7,321 > 1,989). Auditor professional skepticism has a significant effect on the accuracy of giving opinions by public accountants by 44.2%, hypothesis testing is obtained t count > t table or (6.781 > 1.989). Professional ethics and professional skepticism of auditors simultaneously have a significant effect on the accuracy of giving opinions by public accountants with the regression equation Y = 7,494 + 0,418X1 + 0,441X2 and the contribution of influence is 62.4%, hypothesis testing is obtained F count > F table or (47.347 > 2,770).